The Green Hazards: A Meta-Analysis of Green Tobacco Sickness - Achalli, Sonika; Shetty, Shishir Ram; Babu, Subhas G (International Journal of Occupational Safety and Health, 2012)
Green Tobacco Sickness (GTS) has been one of the unexplored areas of occupational health safety. The condition mainly affects the tobacco harvesters. The condition is prevalent in Asian and South American tobacco harvesters. Although transient, the condition can affect multiple organ systems. The objective of this review is to extensively discuss the background, epidemiology, clinical features and measures to counter the problem. A literature search of Medline with terms such as “green”, “tobacco” and “sickness” was done covering years 1970-2007. All studies, reviews and commentaries on health effects of farming green tobacco and preventing the disease were included. Green Tobacco Sickness is caused by the absorption of nicotine through the skin from wet tobacco plants who have direct contact with tobacco plants during cultivation and harvesting. The early symptoms often include headache and nausea followed by vomiting, weakness, pallor, dizziness, headaches, increased perspiration, chills, abdominal pain, diarrhoea, and increased salivation which may also progress to extreme conditions like prostration, shortness of breath, and occasional fluctuations in blood pressure or heart rate. The duration of the illness is usually between one and three days. The use of protective, water-resistant clothing, chemical-resistant gloves, plastic aprons and rainsuits with boots and socks has reduced the chances of contracting GTS. It is important to educate the tobacco workers and the employers about GTS in order to reduce its incidence. An international level awareness campaign has to be taken up and more stringent workers safety regulations have to be formulated. DOI: http://dx.doi.org/10.3126/ijosh.v2i1.4963 International Journal of Occupational Safety and Health, Vol. 2 No. 1 (2012) 11-14